2022
DOI: 10.1111/bjc.12404
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of third wave cognitive behavioural therapies for children and adolescents: A systematic review and meta‐analysis

Abstract: Objectives: Third wave cognitive behavioural therapies are increasingly used with children and adolescents. This meta-analysis aimed to determine the effectiveness of four third-wave interventions (acceptance and commitment therapy, compassion focused therapy, mindfulness-based cognitive therapy, and metacognitive therapy) for youth. Methods: Four electronic databases were used to identify randomized controlled trials, which tested effects related to health, well-being and functioning. Sensitivity analyses con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…The third-wave CBT: The cluster "CBT" is often considered the most recognized psychological intervention for children and adolescents with depression, which can help people learn to identify relationships between cognition, behavior, and mood, and break the cycle of depression by changing distorted cognition or avoidance behaviors[ 11 ]. In recent years, the third-wave CBT approach has been becoming popular, and promising results for the use of third-wave CBT with youth were found in a large meta-analysis[ 8 ]. By contrast to traditional syndrome-specific CBT, the third-wave CBT has become more flexible and process-focused[ 7 ], which targets core psychological processes of change that are functionally important to long-term outcomes in psychological disease[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third-wave CBT: The cluster "CBT" is often considered the most recognized psychological intervention for children and adolescents with depression, which can help people learn to identify relationships between cognition, behavior, and mood, and break the cycle of depression by changing distorted cognition or avoidance behaviors[ 11 ]. In recent years, the third-wave CBT approach has been becoming popular, and promising results for the use of third-wave CBT with youth were found in a large meta-analysis[ 8 ]. By contrast to traditional syndrome-specific CBT, the third-wave CBT has become more flexible and process-focused[ 7 ], which targets core psychological processes of change that are functionally important to long-term outcomes in psychological disease[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, no papers have been published in terms of PIDCA using bibliometrics. According to the papers we reviewed initially, there has been a major shift in the mainstream of psychotherapy paradigm in the late 19 th and early 20 th century[ 7 ], as well as a large number of emerging studies on child and adolescent psychotherapy conducted over the past 10 years[ 8 ]. Therefore, considering the developmental process and growing trend of psychotherapy, we conducted a bibliometric analysis of PIDCA from 2010 to the present to systematically introduce the knowledge structure and theme trends through data mining and mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding typical lengths of CBT with youth, protocols tend to range from 10 to 16 weekly sessions, with extensions to 20 sessions found to be helpful and common (Kagan et al, 2021). Perkins et al (2022) reported intervention durations varying from a single 30-min session to 50 hr of therapy over 20 weeks in meta-analysis of third-wave CBTs for youth.…”
Section: Core Principles and Research Behind Ccpt And Cbt Applied To ...mentioning
confidence: 99%
“…Conventional approaches to therapy with children are vast and wellreviewed, yet lack availability (Boekhoven et al, 2012). For example, cognitive behavioural therapy has proven to be effective amongst a wide variety of youth populations (e.g., Perkins et al, 2022;Wuthrich et al, 2023), but it is not as easily accessible (Dubé et al, 2019). Conversely, unconventional approaches to treatment such as art-based interventions have been less studied, but have the potential for wider availability (Boekhoven et al, 2012).…”
Section: Access To Mental Health Servicesmentioning
confidence: 99%